The Form, Function, and Meaning of the Suffix - an in Indonesian - Praptomo Baryadi Isodarus (Journal Of Social Science (JoSS), 2026)
This research examines the suffix -an in Indonesian to formulate its rules of form, function, and meaning in forming polymorphemic words. Data were collected from the 2023 online edition of the Kamus Besar Bahasa Indonesia, national newspaper articles (February–May 2025), and introspective data from the researcher's competence as an Indonesian speaker. The data were analyzed using the distributional method with the immediate constituent analysis technique and paraphrasing techniques, and the identity method. The results reveal three main findings. First, regarding form, the suffix -an attached to base forms ending in vowels /i/, /u/, /a/, and diphthongs /ay/, /au/ undergoes morphophonemic processes with the addition of sounds [y], [w], and [?], while attachment to consonant-ending base forms causes no change. Second, regarding function, the suffix -an forms nouns when attached to verb and noun base forms, and forms numerals when attached to numeral base forms. Third, regarding meaning, the suffix -an conveys 18 grammatical meanings, including tool, place, result, container, unit, and collective meanings. This research provides a comprehensive reference for teaching, learning, and further studies in Indonesian morphology.